Synthesis and Characterization of Zeolite A from Alkaleri Kaolin using Conventional Hydro Thermal Synthesis Technique - Adamu Abubakar; Nasiru Yahaya; Wilson Lamayi (Nanochemistry Research)
Zeolite A was synthesized via a two-step hydrothermal transformation of kaolin. The kaolin was first transformed to meta kaolin by calcination at 600OC, then treated with 3M NaOH solution (1:5 ration) in a stainless-steel autoclave with a teflon liner. The mixture was heated to 121°C for 2h to insert the sodium ions into the metakaolin structure. The treated kaolin clay was washed three times with deionized water to remove the excess unreacted NaOH, filtered and dried in an oven at 100°C overnight. Different analytical techniques were used to characterize the synthesized  Zeolite A and the individual zeolie/metal oxide nanocomposites including X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive x-ray (EDX), X-ray fluorescence (XRF), Furrier transform infrared (FTIR), and Brunnuer Emmett teller (BET) analysis. FTIR confirmed the presence of Si-O, Si-Al, Al-O, and metal oxygen bonds. SEM/EDX revealed a cubic morphology with some bigger particles that are mono dispersed and partially spherical, along with different compositions of the elements present. XRD showed a face-centered cubic (FCC) structure with 25.73 nm lattice, while XRF confirmed the presence of SiO2, Al2O3 as well as with different major and trace metal oxides. The BET analysis showed 3.9457 and 4.3044 (m2/g), 0.6032 and 0.5598 (cm3/g), 603.087 and 617.503(Ǻ) for both the kaolin clay and the synthesized zeolite A, respectively. The results of this synthesis route demonstrate that Zeolite A was successfully synthesized.